Perancangan Butik “Pusat Grosir Muslim (PGM)” dengan Pendekatan Sense of Place - Kosalim, Alvira Zerlinda Kosalim; Anggraini, Lya Dewi (Universitas Ciputra Surabaya, 2021)
The focus of this research is designing buildings and spaces using the factors forming sense of place. The goalis to create a space that has aesthetic value, comfort, and can provide a sense of attachment between the userand the building so as to add value to residential, commercial, and public spaces. The methods used in thisdesign are observation and analysis, data collection, and literature study. From this method it was found thatthis design uses (1) fulfillment of the human senses, (2) forms of identity and (3) comfort, (4) pays attention tothe aesthetic side, so that (5) can design memory or experience in space or buildings. From this it is expectedto create a space that can support the self-actualization of its users. The results of this design obtained abuilding with the concept of fun and glass, where the building can support the concept of a boutique with anattractive window display and interior. The use of the forming factor of sense of place is also found in interioraesthetics, comfort with ergonomic furniture, and fulfillment of the human senses to form a sense of place.Spatial planning in building plans is also a method of solving problems and establishing comfortable spaces.By fulfilling the factors forming the sense of place, it is expected to form a sense of the user’s attachment tothe building.